International Experience of Islamic Financial Organizations (Texas Journal of Multidisciplinary Studies, 2022)
The article describes the foreign experience of Islamic financial organizations. In particular, thearticle discusses the current state of Islamic financial indicators of the leading countries in the field ofIslamic finance, the specific features of the activities of Islamic financial organizations in the CIS countriesare shown.